1983
DOI: 10.1093/ajcn/37.4.509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise on riboflavin requirements of young women

Abstract: The riboflavin requirement of young women during periods of sedentary living and exercise was determined during a 12-wk metabolic study. The study was divided into a 6-wk no exercise period followed by a 6-wk exercise period in which subjects jogged around a track for 20 to 50 min/day. Twelve subjects, aged 19 to 27 yr, were fed a basic diet containing 0.6 mg riboflavin/1000 kcal of intake. Riboflavin intake was increased by 0.2 mg/1000 kcal increments by provision of riboflavin in a glucose polymer mixture. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 12 publications
1
29
0
1
Order By: Relevance
“…Using erythrocyte glutathione reductase activation coefficient (E-GRAC) as an indicator of riboflavin status in females, Belko et al 69 reported a 15% increase in daily riboflavin requirement during increased moderate physical exercise. Two subsequent studies by the same group 70,71 seemed to support the finding.…”
Section: Vitamins Of the B-complex Groupmentioning
confidence: 99%
“…Using erythrocyte glutathione reductase activation coefficient (E-GRAC) as an indicator of riboflavin status in females, Belko et al 69 reported a 15% increase in daily riboflavin requirement during increased moderate physical exercise. Two subsequent studies by the same group 70,71 seemed to support the finding.…”
Section: Vitamins Of the B-complex Groupmentioning
confidence: 99%
“…Using an erythrocyte glutathione reductase activation coefficient (EGRAC) >1.25 as evidence of riboflavin deficiency, Belko and colleagues (7) found that physically active young women needed between 0.63 and 1.4 mg/1,000 kcal. When overweight women on a caloric restricted diet were examined, it was found that 0.8 mg riboflavin1 1,000 kcal was not adequate during periods of exercise or nonexercise (8).…”
Section: Vitamin Needs During Exercisementioning
confidence: 99%
“…It has been proposed that thiamin [30] and ribo flavin [6] requirements are higher in the phys ically active, but these viewpoints have also been questioned [31,32], It is possible that the lack of changes in thiamin and riboflavin status indicators during the present exercise program was due to adequate dietary intakes or that the increase in total daily EE was not large enough.…”
Section: Discussionmentioning
confidence: 94%